An Industrial systems design study on MOD Electronics Repair Center - Abarquez, Joselito (College of Engineering, 2004)
MOD Electronics Repair Center is a service center that specialized in the repair of electronic appliances such as televisions, radio components, VHS, DVD, and VCD company still continues its pursuit of its mission-vision, that of providing its clients with a fast and excellent service at a very reasonable price and that of becoming a household name in the electronics repair industry. Based on an industry as well as an internal analysis using the tools Seven S Model, Five Forces Model, and SWOT Analysis, the group formed a strategy using the Ansoff Matrix which suggested a market development strategy, which includes the pursuit of additional market segments or geographical regions, and a focus strategy that concentrates on the company having a low cost advantage. From the Stream Diagnosis Analysis, the group identified three major areas of concern: (1) revenue losses, (2) lack of check and balance, and (3) insufficient facility space. With this, the group, using the root cause verification matrix, verified for root causes for these problems, namely (1) vague job descriptions, (2) vulnerable company forms, (3) lack of marketing plan, and (4) unclaimed service appliances. To address these problems, the group recommended a marketing plan based on customer surveys regarding product (which is service), price, placement, and promotions. The group also recommended an improvement in internal control by subdividing the duties of the branch administrator and the technicians, and also through revisions on the company's systems and procedures. Recommendations were also presented regarding the unclaimed appliances. Guidelines and agreements between the company and the customer, wherein a 30-day service guarantee, a 15-day claiming period, and a 15-day reclaiming period with a fine, as well as an unclaimed appliance inventory control, are proposed. All these recommendations are in line with the company's mission-vision, as well as the appropriate strategies (market development and focus strategy) that the company should pursue. The group proposed an implementation plan for the company which includes personnel briefings on major systems and procedure changes to be conducted everyday 30 minutes after opening. A Gantt Chart is presented by the group to guide management implement the group's recommendations. The group recommends further studies to determine the feasibility of installing a computerized information system and a detailed feasibility study must be done by the company before pursuing any expansion plans.